-7n+10n=-33

Simple and best practice solution for -7n+10n=-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7n+10n=-33 equation:


Simplifying
-7n + 10n = -33

Combine like terms: -7n + 10n = 3n
3n = -33

Solving
3n = -33

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '3'.
n = -11

Simplifying
n = -11

See similar equations:

| (2(x^(1/2)))^2 | | 5t-92=t | | 1+7x+3x=21 | | 4p-32=p+31 | | 3m+5n=7 | | y=4y-30 | | -1=x-6+5 | | 2m=n-4 | | 21=4v-7v | | 9b-22=7b-16 | | -2(1-6r)=-2+4r | | 4v+6=41-3v | | 4s+14=2s+66 | | 3x^2+6x=168 | | p+p+64=180 | | -3(x-1)=-2x-3 | | 2a-21=a | | 12x-11y=23 | | 3/13=u/10 | | 5(2x+5)-1=-2x | | 2b-48+2b-96=180 | | 3u-64=u | | 10y+9=13y+3 | | 3n+4(5n+2)=8+3n | | 16z-21+2z+39=180 | | -3(1-5m)+4=1-2m | | 7=an-1+-15 | | 4c-65=5c-85 | | 4c-65=5c-68 | | -2+3p=6p-4-2p | | 7y+73=4y+94 | | -5+6m=5m-8 |

Equations solver categories